PENYULUHAN MANFAAT PENANAMAN TANAMAN OBAT (TOGA) DI MASA PANDEMI DIDESA CIBIRU HILIR KECAMATAN CILEUNYI KABUPATEN BANDUNG - Ooy Siti Halimah; Nurul Noviyanti; Tania Aldyla; Nisa Aulia Dwiyanti; Silvia Alfi Nurfatwa; Giadi Fachrul Husaeri Dewia; Aldi Gilang Ramadhan; Zainal Abidin; Ayu Dharmayati (Jurnal Pengabdian Kepada Masyarakat Babakti, 2021)
The covid-19, is the thing that contains the emergence of various kinds of problems at this time. The economy, health and so on are affected by this covid-19 virus. Until now, the world has entered the Covid-19 pandemic, which requires everyone to follow standard health protocols in order to maintain health as a top priority. In response to the COVID-19 pandemic, a program from universities, carried out the student study service activities with the theme "Bangkit Menuju Masa Bebas Pandemi Covid-19" in Cibiru Hilir Village,Cileunyi,Bandung. The purpose of this service is to overcome problems that arise in communities affected by the Covid-19 virus. One of the programs of this activity is the planting of Toga plants such as ginger, turmeric, and aromatic ginger/sand ginger. Where this toga plant itself has a function to increase the body's immune system so that it can avoid the covid-19 virus. The result of this activity is that we hope that people will be more aware of the importance of health by making herbal medicine from natural ingredients.